Isolamento reprodutivo e diversidade genética em Erythroxylum (Erythroxylaceae) P. Browne - BARRETO, Laís Leite (2018)
The Erythroxylaceae Kunth family is well represented in Brazilian flora, with 9 sections of the genus distributed in the Amazon, Caatinga, Cerrado and Atlantic Forest. The region with the greatest diversity is the Northeast (77), where the state with the greatest wealth is Bahia (56). Considering this scenario, we can affirm that studies involving populations of the genus Erythroxylum, where individuals have intermediate morphology, are essential to assess the intensity of reproductive barriers between species, especially because the great most of them occur in sympathy. Based on this information, we use as a model an area of ​​montane forest in northeastern Brazil where three dystyllic species of Erythroxylum (Erythroxylum citrifolium, E. pauferrense and E. simonis) occur that have overlapping flowering periods and similarities in floral characteristics. The reproductive isolation between such species was investigated through studies of phenology, reproductive and molecular biology, which, respectively, indicated the levels of overlapping flowering seasons, intra and inter specific gene flow, details of pollinator groups and genetic structure populational. The field study was carried out in the Mata do Pau-ferro State Park (6 ° 58 '12' S and 35 ° 42 '15' W), where we collected phenological data on flowering, morphometry and floral biology, pollination, reproductive system. For the assessment of genetic diversity and population structure, random collections of fresh leaves were carried out in some states in Brazil, where we obtained samples from 26 populations of different species. None of the studied species showed reciprocity between floral morphs or isoplethia. This variation may be linked to the fact that the species are self-compatible, due to a break in the heterostilia mechanism. Controlled pollination treatments showed that there is compatibility between the different morphs and interspecific compatibility between E. pauferrense and E. simonis as a pollen donor or recipient, proving that the pre-zygotic reproductive barriers are weak and favor the hybridization process between them. Erythroxylum citrifolium, although it does not present reciprocal hercogamy between morphs, also did not show compatibility between identical morphs or at interspecific crosses. From samples collected, DNA samples were extracted for sequencing and amplification, using the PCR technique. In addition, a primer library was built, using the Iluminna II platform, of which 2 new primers were tested and optimized, proving capable of amplifying in different species of the genus, thus contributing to a better understanding of the population structure of several species of Erythroxylum. In addition to the primers developed in this study, primers developed from Australian species of Erythroxylum were tested, of which 4 were successful in amplification. From the data obtained, individual matrices were constructed for the ITS and trnL regions and each one was analyzed individually using Bayesian and parsimony analysis. Phylogeny was used to compare the relationships between Erythroxylum species, covering the geographical distribution of the genus. A Maximum Parsimony tree revealed both geographic and taxonomic partitioning in clades representing species from Africa, Asia-Pacific and the New World (Tropical Americas). Our results show that: in all analyzes the genus Erythroxylum is paraphyletic and the sections are also paraphyletic, which suggests an independent and non-linear evolutionary relationship between the species of Erythroxylum, the analyzes identified significantly different genetic groups in Erythroxylum suggesting that the current one intragenic classification of this genus needs to be revised.